2020
DOI: 10.1039/d0ce00914h
|View full text |Cite
|
Sign up to set email alerts
|

Influence of crystal packing on the thermal properties of cocrystals and cocrystal solvates of olanzapine: insights from computations

Abstract: A multicomponent supramolecular host with adaptive guest accommodation abilities is observed in the cocrystal solvates of the olanzapine–hydroquinone system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 91 publications
0
24
0
Order By: Relevance
“…17 There are few studies on the solvates which are built entirely by weak interactions, like C-H•••O and C-H•••π. 18,19 Despite the increasing interest in solvates, 15,16 we still lack a general understanding of the solvate formation and structure−stability relationships, especially the role of weak interactions.…”
Section: Introductionmentioning
confidence: 99%
“…17 There are few studies on the solvates which are built entirely by weak interactions, like C-H•••O and C-H•••π. 18,19 Despite the increasing interest in solvates, 15,16 we still lack a general understanding of the solvate formation and structure−stability relationships, especially the role of weak interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Table reveals the summary of olanzapine screening that had 25 positive results out of 52 experiments, including the previously reported cocrystals/salts of Olanzapine. , Figure S2 shows the experimental evidence for olanzapine multicomponent solid forms. To qualitatively compare these predictive approaches, the ROC plot and the respective area under the curve (AUC) for each method are illustrated in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…37 This endothermal desolvation during the photodimerization is accompanied by reduction of density lowering burst speeds. 38 The splitting into pieces of CP 2 may be due to the strain induced by the loss of guest solvent as well as photodimerization. 29 Importantly, the crisscross aligned CQC bonds in the CH 3 -bpeb pairs (CP 3 ) may slow down or even prohibit the reaction though it can undergo the pedal-like motion to a parallel orientation for photodimerization.…”
Section: And Fig S13 S14 Esi †)mentioning
confidence: 99%
“…37 Endothermal desolvation also buffers the strain of reaction by dissipation of energy. [37][38][39] We herein report the modulation of the PS effects by governing the ). Thermogravimetric analysis (TGA) revealed that CP 1 -CP 4 were stable up to 340 1C (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation